Pancytopenia and Kaposi sarcoma indicators of HIV infection diagnosis: A case report - Monica Padurariu-Covit; Gabriela Lupasteanu; Manuela Arbune (Romanian Journal of Infectious Diseases, 2021)
During HIV infection, hematological manifestations are frequently associated with various pathogenic mechanisms, which require a multidisciplinary approach. We present the case of a 57-year-old patient with pancytopenia associated with Kaposi's sarcoma, as indicative manifestations of the acquired immunodeficiency syndrome. The late diagnosis of HIV infection, in the stage of severe immunosuppression, the association of opportunistic neoplasia, delayed oncological therapy and the development of immune reconstruction syndrome after starting antiretroviral therapy have contributed to the severe evolution and death of the patient.